Rancangan Sistem Informasi Akuntansi Keuangan Perusahaan Agen Gas LPG Berbasis Google Spreadsheet Sesuai Sak Entitas Privat - Muhammad Tezar (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
The company's financial report is a very important document for accountability of management within a company. With the advancements in technology and widespread internet access, Google Spreadsheet was chosen to prepare the company's financial report due to its very easy-to-use nature and the ability to be accessed from various devices such as gadgets, laptops, personal computers, and tablets. Many companies have already implemented integrated computer-based accounting software applications, but they still use Google Spreadsheet or Excel as initial data or backup data for their financial records. Many mosques still use traditional methods for their financial bookkeeping, similar to other mosques. These mosques still record their accounting manually, mainly due to limited funds to purchase integrated accounting software. Therefore, it is necessary to design a financial reporting model for companies using Google Spreadsheet. It is expected that this can help other companies that want to prepare financial reports easily, inexpensively, and in accordance with the applicable Financial Accounting Standards for Private Entities effective from January 1, 2025.